Peru : Accounting and Auditing - World Bank (Washington, DC, 2013)
The report provides an assessment of accounting, financial reporting, and auditing practices within the corporate sector in Peru, using International Financial Reporting Standards (IFRS), and International Standards on Auditing (ISA) as benchmarks, drawing on international experience and best practices in that field. This Report on the Observance of Standards and Codes (ROSC) Accounting & Auditing review included the analysis of a sample of 20 published audited financial statements, and found that financial reporting standards broadly complied with by Peruvian corporations, although a number of cases of departures from IAS, and possibly from ISA, were noted. This points the need to strengthen the enforcement of financial reporting and auditing requirements for entities of public interest. The review also noted that existing arrangements for the licensing of auditors do not provide compulsory minimum academic course content in accounting and auditing, nor do they include professional examination; moreover, continuing education requirements are not effectively followed. This is detrimental to the quality of the accounting and audit practice in the country. The lack of quality control of auditors is also a cause of serious concern. The report offers several policy recommendations aimed at strengthening the regulatory framework governing accounting and auditing, including establishing an independent oversight body for the audit profession, that would ensure qualified auditors with a strong academic background, and professional skills, and that they comply effectively with both ISA and applicable ethical requirements. Another recommendation of this ROSC is that large, non-listed companies be required to have their financial statements audited, and to publish these financial statements through CONASEV - National Supervisory commission of Enterprises and Securities.